Potency of Endophytic and Rhizospheric Bacteria of Akar Kucing (Acalypha indica Linn.) as Antibacteria against Klebsiella pneumoniae - Rahmawati, Fitriana Dewi; Suharjono, Suharjono (Journal of Tropical Life Science, 2021)
ABSTRACTÂ Prevalence of pneumonia in Indonesia was 2% in 2018. Treatment of pneumonia using antibiotics caused resistant of pathogenic bacteria. Endophytic and rhizospheric bacteria of Acalypha indica Linn. can be used as alternative for treatment of pneumonia. This study aims to analyze the potency and identify of endophytic and rhizospheric bacteria of the Acalypha indica Linn as an antibacteria of Klebsiella pneumoniae. The research included isolation and purification of endophytic and rhizospheric bacteria of the Acalypha indica Linn, antagonistic assay of bacteria cell culture, antibacterial assay of bacteria metabolites; and identify of potential isolates based on 16S rDNA sequence similarity. The results showed that number of rhizosphere bacteria 6.83 x 105 CFU/gram was more than endophytic bacteria 1.78 x 104 CFU/gram. Diversity of rhizosphere bacterial 0.72 was higher than endophytic bacteria 0.62. The rhizospheric bacteria RU112B and RU315B had highest activity to inhibit growth of Klebsiella pneumoniae. Both isolates RU112B and RU315B were identified as Staphylococcus saprophyticus with similarity 99.83% and Luteimonas terrae with similarity 99.67% respectively.Â Keywords: Acalypha indica Linn, endophytes, Klebsiella pneumoniae, rhizosphere